Equilibrium solubility versus intrinsic dissolution: characterization of lamivudine, stavudine and zidovudine for BCS classification - André Bersani Dezani; Thaisa Marinho Pereira; Arthur Massabki Caffaro; Juliana Mazza Reis; Cristina Helena dos Reis Serra (Universidade de São Paulo, 2013)
Solubility and dissolution rate of drugs are of major importance in pre-formulation studies of pharmaceutical dosage forms. The solubility improvement allows the drugs to be potential biowaiver candidates and may be a good way to develop more dose-efficient formulations. Solubility behaviour of lamivudine, stavudine and zidovudine in individual solvents (under pH range of 1.2 to 7.5) was studied by equilibrium solubility and intrinsic dissolution methods. In solubility study by equilibrium method (shake-flask technique), known amounts of drug were added in each media until to reach saturation and the mixture was subjected to agitation of 150 rpm for 72 hours at 37 ºC. In intrinsic dissolution test, known amount of each drug was compressed in the matrix of Wood's apparatus and subjected to dissolution in each media with agitation of 50 rpm at 37 ºC. In solubility by equilibrium method, lamivudine and zidovudine can be considered as highly soluble drugs. Although stavudine present high solubility in pH 4.5, 6.8, 7.5 and water, the solubility determination in pH 1.2 was not possible due stability problems. Regarding to intrinsic dissolution, lamivudine and stavudine present high speed of dissolution. Considering a boundary value presented by Yu and colleagues (2004), all drugs studied present high solubility characteristics in intrinsic dissolution method. Based on the obtained results, intrinsic dissolution seems to be superior for solubility studies as an alternative method for biopharmaceutical classification purposes.